Car management using radio frequency identification (RFID) - Chew, Pei Ting (2011)
Radio Frequency Identification (RFJD) is a wireless communication technology that uses radio-frequency waves to transfer information between tagged objects and readers without line of sight.Radio frequency identification (RFID) has been identified as one of the ten greatest contributory technologies of the 21st Century.This technology has found a rapidly growing market,and an increasing variety of enterprises are employing RFID to improve the efficiency of their operations and to gain competitive advantage.In many country RFID have been used to check n record the cars flow. RFJD tags were found to be better than the car sticker and their performance was also measured to be well above that of car stickers.The RFID system is built from three basic components which are the reader also known as the detector that may be used as to read or write device,the transponder also known as tag which is located on the object to be identified and antenna.This paper presents the implementation of RFID technology to manage the car flow in the company.This is accomplished by integrating RFID technology together with linking of database.